Broadband Adoption In Malaysia - Zanariah, Mansor (2010)
This paper tends to summarize the findings of a research program aimed at outlining the broadband adoption level by respondents at random and their opinion and satisfaction level in using the services. It is also to provide a helicopter view on the situation of broadband adoption in Malaysia and to confirm on priorities factors that need to be reviewed or provided for broadband adoption to be accelerated. Broadband internet offers potential to increase the international competitiveness and economic growth of a country by accelerating the growth and deployment of emerging electronic services including e-commerce and e-govemment. Thus, there are influencing factors that can affect broadband adoption. Influencing factors like affordability, knowledge, skill of using computer, readiness in providing broadband equipment (like modem, PC, cable etc) and the behavioural intention (purpose) in obtaining broadband service perceived to ensure the success of broadband adoption. This research is to understand on the relationship of these influencing factors with broadband adoption in Malaysia. Research via survey was conducted to understand the situations and find out the overall picture of the demographic of broadband adopters, the connectivity being used, the main purpose of using broadband, the experiences they have on using broadband and the effectiveness of current broadband provider (limited to TM only). Respondents are also expected to determine the priority level of selected factors that they think can help to ensure that broadband can be adopted effectively in Malaysia. Descriptive· analysis, cross tabulation and regression was done to determine the relationship hypothesis between behavioural intention with necessities, awareness and readiness.